Asupan Suplemen Bukan Determinan Kejadian Stunting Anak balita (1-3 Tahun) - Didik Hariyadi (Poltekkes Kemenkes Pontianak, 2016)
Abstract: Supplement Intake Not Determinants Stunting Events Children (1-3 Years). This study aims relationship supplement intake with the incidence of stunting among Children aged 1-3 years who live in urban areas Kubu Raya. An observational study with the cross-sectional design. The research was conducted in Kubu Raya in August to November 2014. Measurement of nutritional status using indicators PB/U. Supplement intake asked to interview. Statistical analysis was performed using Chi-square test.The results showed the percentage of stunting in Children aged 1-3 years in the amount of 39.51%.The most consumed form of supplements which are of the type syrup as much as 34.6% of 82.7% respondents toddler supplements. No significant relationship exists between supplement intake with the incidence of stunting in Children aged 1-3 years in the urban area of Kubu Raya.Abstrak: Asupan Suplemen Bukan Determinan Kejadian Stunting Anak balita (1-3 Tahun). Penelitian ini bertujuan hubungan asupan suplemen dengan kejadian stunting pada anak balita usia 1-3 tahun yang tinggal di daerah urbanKubu Raya. Penelitian ini bersifat observasional dengan rancangan cross sectional. Penelitian dilaksanakan di Kabupaten Kubu Raya pada bulan Agustus sampai November 2014. Pengukuran status gizi menggunakan indikator PB/U. Asupan suplemen ditanyakan dengan wawancara. Analisis statistik dilakukan dengan menggunakan uji Chi square.Hasil penelitian menunjukan persentase kejadian stunting pada balita umur 1-3 tahun yaitu sebesar 39,51%. Sebanyak 82.7% balita responden mengonsumsi suplemen, dengan bentuk suplemen yang terbanyak dikonsumsi adalah dari jenis sirup sebanyak 34.6%.Tidak ada hubungan yang bemakna antara asupan suplemen dengan kejadian stunting pada balita umur 1-3 tahun di daerah urban Kubu Raya.